2010
DOI: 10.1093/jac/dkq222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, and comparison, of human clinical and black-headed gull (Larus ridibundus) extended-spectrum  -lactamase-producing bacterial isolates from Kalmar, on the southeast coast of Sweden

Abstract: The finding of CTX-M-type ESBLs in E. coli isolated from black-headed gulls in Sweden, where 'background resistance' is low, is consistent with an ongoing environmental spread of these plasmid-borne resistance genes. The results indicate that a potential for transfer between the human population and environment exists even in countries with a low level of antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 18 publications
5
77
1
2
Order By: Relevance
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussionmentioning
confidence: 45%
“…In this study, the ESBLcontaining E. coli isolate, classified in the A phylogroup, was more sensitive to the antimicrobial compounds tested than ESBL-positive E. coli isolates recovered from other wild animals in mainland Portugal Poeta et al, 2009;Pinto et al, 2010;Radhouani et al, 2010a). Moreover, the b-lactamase genes detected in our isolate (bla CTX-M-14 and bla SHV-12 ) were also found in wild birds in Sweden (Bonnedahl et al, 2010) and Poland (Literak et al, 2010). How these wild birds acquired VRE and ESBL-containing E. coli is unclear.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Recently, E. coli ST57, ST156, and ST371, all producing ESBLs, have been recovered from chickens and turkeys in different countries in Europe and North America (Bonnedahl et al, 2010;Randall et al, 2011;Simoes et al, 2010) and ESBL-producing, verocytotoxin-producing E. coli (VTEC) isolates have also been described 10 .…”
Section: Escherichia Colimentioning
confidence: 99%
“…CTX-M-15-producing E. coli ST156 in gulls sampled in southern France, chickens and turkeys in Portugal and the UK has recently been reported (Bonnedahl et al, 2010;Randall et al, 2011;Simoes et al, 2010). CMY producers of major clonal complexes have been reported among poultry, although transmission to humans has not been demonstrated (Cortes et al, 2010).…”
Section: Escherichia Colimentioning
confidence: 99%